2019
DOI: 10.1186/s12964-019-0371-1
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of fibroblast growth factor receptor 1 trafficking and function by extracellular galectins

Abstract: Fibroblast growth factor receptors (FGFRs) are integral membrane proteins that transmit signals through the plasma membrane. FGFRs signaling needs to be precisely adjusted as aberrant FGFRs function is associated with development of human cancers or severe metabolic diseases. The subcellular localization, trafficking and function of FGFRs rely on the formation of multiprotein complexes. In this study we revealed galectins, lectin family members implicated in cancer development and progression, as novel FGFR1 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 62 publications
1
37
0
Order By: Relevance
“…Recently, we have reported that galectin family members, galectin‐1 and galectin‐3, interact with the sugar chains of the glycosylated extracellular domain of FGFR1, regulating activity and trafficking of the receptor [31]. Using competitive BLI, we studied the effect of B‐Fc and T‐Fc binding on the receptor interaction with galectin‐1 and galectin‐3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, we have reported that galectin family members, galectin‐1 and galectin‐3, interact with the sugar chains of the glycosylated extracellular domain of FGFR1, regulating activity and trafficking of the receptor [31]. Using competitive BLI, we studied the effect of B‐Fc and T‐Fc binding on the receptor interaction with galectin‐1 and galectin‐3.…”
Section: Resultsmentioning
confidence: 99%
“…To study which CIE route mediates the endocytosis of T‐Fc, we employed siRNA‐mediated knockdown of key CIE‐specific proteins. We downregulated expression of dynamin‐2, which is involved in CME and in several CIE routes, galectin‐3, FGFR1‐binding protein mediating the clathrin‐independent carriers (CLIC) pathway, and ROCK1 and ROCK2 proteins involved in RhoA‐dependent CIE [31,51]. As a control, we knocked down a μ2 subunit of the adaptin‐2 complex (AP2μ2), an CME adaptor [53,54].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations